Measuring The Role of Science as Basis of Student Character Development in Islamic Education Learning - Nur Chanifah (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
The purpose of this study is to analyze the role of science as the basis for student character formation in Islamic Religious Education (PAI) learning. This study is important to carry out considering that the problem of the nation's moral deterioration is getting heavier. There are many cases of sexual violence, narcotics abuse, plagiarism, and others. Islamic Religious Education is one of the subjects that plays a role in shaping student character. For this reason, there needs to be improvements and improvement in the quality of teaching. One way is to use science as an approach to spreading Islamic Religious Education. The method used is a literature review by reviewing several relevant literature. Data processing techniques with three stages, namely editing, classifying, and concluding. Meanwhile, the analysis uses content analysis. The results of the study show that to form the character of students, science plays a role as the basis or learning approach of Islamic Religious Education. In science, there are several aspects that can be used to build morals or character, such as observing/observing, classifying, communicating, measuring, predicting, and making inferences, analyzing, conducting investigations, and conducting experiments. From this process, students practice with scientific attitudes such as logical and sequential thinking (systematic), creative, innovative, rich in inspiration, and sportsmanship